Can severe drought reverse woody plant encroachment in a temperate Australian woodland?. (10th March 2014) - Zeeman, Ben J.; Lunt, Ian D.; Morgan, John W.
Abstract: Question: Increases in the cover of woody plants have been documented in woodland, savanna and grassland ecosystems across the globe, commonly attributed to changes in land use or disturbance regimes. This is often thought to result in alternative stable states resistant to reversal. However, some multi‐decadal‐scale studies have found woody plant cover fluctuates according to variations in rainfall. After a decade‐long El Nino event, we ask: can severe drought reverse woody plant encroachment in a temperate Australian woodland? Location: Temperate coastal woodland in Victoria, SE Australia that has remained unburned for over a century. Methods: Using data spanning 41 yr, changes in basal area and tree density were assessed for the major woody species in a eucalypt woodland. Data were used to determine whether a decade of severe drought (1997–2009) had reversed a previously identified phase of woody plant encroachment (1971–1996). Results: After an increase in stand density between 1971 and 1996, attributed to an increase in the fire‐sensitive species Allocasuarina littoralis, total tree density then declined by 42% between 1996 and 2012. Changes in tree density differed across dominant woody species ( A. littoralis −34%, Allocasuarina verticillata +26%, Acacia pycnantha −78%, Banksia marginata −73%, Eucalyptus spp. −97%), and seedling recruitment almost completely ceased for all species. However, the basal area of A. littoralis (having almost doubled between 1971 and 1996) had continued to increase by 75%, with increases highest in areas where initial basal area was lowest. Despite this increase, total stand basal area remained relatively stable, with an increase of 5%, because of a combined decline in basal area for all other species of 62%. Conclusion: Despite the most severe drought on record, site occupancy – as measured by basal area – did not decline between 1996 and 2012. Thus, severe drought did not reverse woody plant encroachment. Rather, findings were consistent with the previous trend of increasing A. littoralis dominance at the expense of other tree species in the long‐term absence of fire. Abstract : In a temperate Australia woodland, we assessed stand data over a period of 41 yr to ask whether woody plant encroachment could be reversed by severe drought. As climate change intensifies, drought is expected to become more frequent and severe in southern Australia. Our results suggest that encroached temperate woodlands can be expected to be resilient to climate change.